Interrelationship Between Specific High-Intensity Intermittent Efforts Ability with Aerobic Capacity and Slow Stretch-Shortening Cycle Utilization in Taekwondo Athletes - Herrera-Valenzuela, T; Aedo-Munoz, E (IOS Press BV, 2022)
BACKGROUND: In taekwondo the ability to repeat high-intensity efforts is characteristic of the sport. The Frequency speed of kick test (FSKT) is frequently used to assess this ability, although its influence on aerobic capacity and dynamic strength characteristics has received less attention in the literature. OBJECTIVE: To examine the relationship between specific high-intensity intermittent efforts with aerobic capacity and slow stretch-shortening cycle utilization in taekwondo athletes. METHODS: Nineteen taekwondo male athletes were assessed by squat jump (SJ), countermovement jump (CMJ), 20-meter shuttle run (20MSR), and frequency speed of kick test multiple (FSKTMULT). From the FSKTMULT, total kicks and kick decrement index [KDI] were calculated. Additionally, from both jump tests, the slow stretch-shortening cycle utilization (Slow SSC Utilization) was determined from the eccentric utilization ratio [EUR], pre-stretch augmentation [PSA], and reactive strength index [RSI]. RESULTS: There were positive and significant correlations between total kicks with 20MSR (r= 0.85; p= 0.00) and SJ (r= 0.66; p< 0.05). The multiple regression model demonstrated that total kicks where significantly influenced by 20MSR (R2= 71%; p= 0.00). Additionally, only EUR and RSI explained total kicks performance to a greater proportion (R2= 76%). CONCLUSIONS: The FSKTMULT total kicks performance is positively correlated and influenced by aerobic capacity and slow SSC utilization. © 2022-IOS Press. All rights reserved.